TINJAUAN YURIDIS PERATURAN GUBERNUR ACEH NOMOR 15 TAHUN 2023 TENTANG PEDOMAN PENGOLAHAN DAN PENGELUARAN GETAH PINUS - Lestari, Rachmatika; Sari, Putri Kemala; Mubarak, Zamzam (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
Aceh Governor Regulation Number 15 of 2023 concerning Guidelines for Pine Sap Processing and Expenditure was issued and signed directly by the Acting Governor of Aceh on May 29, 2023. Since the issuance of this Pergub, the sale of raw pine sap outside the Aceh region has stopped, causing farmers or business actors to be unable to continue trade contracts that have been running with business actors outside Aceh. The results showed that the spirit and purpose of the issuance of this Pergub is so that pine sap which is one of Aceh's Natural Resources can be utilized, managed, have added value, and can increase Regional Original Income which in the end can be used for the prosperity of the people. From Article 7 of the Governor's Regulation it can be seen that the Government of Aceh stops the sale of pine sap outside the Aceh region temporarily until the needs of the Pine Sap processing industry in the Aceh region are met first. However, based on data published by DPMPTSP Aceh in 2021, conditions in the field currently Aceh only has 2 (two) pine sap processing plants, namely in Central Aceh and Gayo Lues, causing pine sap stocks in the region to be abundant, and causing pine sap prices in the Aceh region to be low, which ultimately has an impact on price stability and the economy of pine sap farmers themselves. Therefore, the Government of Aceh must pay attention to various aspects both from philosophical, sociological, and juridical aspects in the formation of Governor Regulation No. 15 of 2023 so as not to cause negative impacts on the economy of the community, especially farmers or pine sap business actors. The advice given is that the Government of Aceh needs to review Governor Regulation No. 15 of 2023, especially related to the economic impact caused, and harmony between other laws and regulations while still paying attention to aspects of the specificity of Aceh itself, so that the enactment of the Governor's Regulation does not actually hamper the productivity that has been carried out by farmers and / or pine sap business actors. Keywords: Gubernatorial Regulation, Processing and Expenditure, Pine Sap